2019
DOI: 10.3390/md17020109
|View full text |Cite
|
Sign up to set email alerts
|

5-O-Acetyl-Renieramycin T from Blue Sponge Xestospongia sp. Induces Lung Cancer Stem Cell Apoptosis

Abstract: Lung cancer is one of the most significant cancers as it accounts for almost 1 in 5 cancer deaths worldwide, with an increasing incident rate. Management of the cancer has been shown to frequently fail due to the ability of the cancer cells to resist therapy as well as metastasis. Recent evidence has suggested that the poor response to the current treatment drugs and the ability to undergo metastasis are driven by cancer stem cells (CSCs) within the tumor. The discovery of novel compounds able to suppress CSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…Natural products and their derivatives contribute to approximately 63% of new drug development. 9 Many studies have shown that myricetin, a flavonoid widely found in tea, fruits, and herbs, has antiproliferative effects on various cancers. [10][11][12] Shih et al found that the invasion and migration ability of A549 cells could be suppressed by blocking the extracellular regulated protein kinases signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products and their derivatives contribute to approximately 63% of new drug development. 9 Many studies have shown that myricetin, a flavonoid widely found in tea, fruits, and herbs, has antiproliferative effects on various cancers. [10][11][12] Shih et al found that the invasion and migration ability of A549 cells could be suppressed by blocking the extracellular regulated protein kinases signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, its anti-cancer activities have been reported against several types of cancer cells, such as colon (HCT116), prostate (DU145) [46], non-small cell lung (H292, H460, and QG56) [47], breast (T47D), and pancreatic (AsPC1) cancer cells [45]. Moreover, a modified form of RT, 5-O-acetyl-renieramycin T, was shown to induce the death of lung cancer stem cells and sensitize cisplatin-mediated apoptosis in lung cancer cells [48]. Our previous study revealed that the effects of RT on the apoptotic mechanism depended on the disappearance of Mcl-1 through the increase in Mcl-1 protein degradation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RT, the renieramycin–ecteinascidin hybrids in the tetrahydroisoquinoline alkaloid family, showed strong cytotoxicity in several cancer cell lines including colon (HCT116), prostate (DU145), non-small cell lung (H292, H460 and QG56), breast (T47D), and pancreatic (AsPC1) cancers [39,53,54,55]. Moreover, our previous study suggested that 5- O -acetyl-renieramycin T, a modified compound of RT, exerted a potential to suppress cancer stem cell (CSCs) growth, which is represented by a decrease in the CSCs markers CD44 and CD133 due to depletion of the protein kinase B (AKT) signal resulting in apoptosis induction of CSCs [56]. However, cell death mechanisms in CSCs and cancer cells might be different since CSCs have special characteristics only found in the stem cell population such as metabolic activities, signaling pathways, and cell cycle regulation [57,58,59].…”
Section: Discussionmentioning
confidence: 99%